Biosynthesis, Characterization, Adsorption and Antimicrobial studies of Vanadium Oxide Nanoparticles Using Punica Granatum Extract - Angham Tariq Ali; Lekaa K. Abdul Karem (مجلة بغداد للعلوم)
This study includes using green or biosynthesis-friendly technology, which is effective in terms of low cost and low time and energy to prepare V2O5NPs nanoparticles from vanadium sulfate VSO4.H2O using aqueous extract of Punica Granatum at a concentration of 0.1M and with a basic medium PH= 8-12. The V2O5NPs nanoparticles were diagnosed using several techniques, such as FT-IR, UV-visible with energy gap Eg = 3.734eV, and the X-Ray diffraction XRD was calculated using the Debye Scherrer equation. It was discovered to be 34.39nm, Scanning Electron Microscope (SEM), Transmission Electron Microscopy TEM. The size, structure, and composition of synthetic V2O5NPs were determined using the (EDX) pattern, Atomic force microscopy AFM. The adsorption experiment was successfully conducted on metal ions M (II), such as Co, Ni, and Cu. The results proved removal simultaneously from water using V2O5NPs based on surface shape on the affinity of three metal ions. The adsorption rate of Ni(II) is the highest one in the time scale and conditions of our experiment at all surfaces, while Co(II) and Cu(II) ions are close in magnitude. The removal efficiencies of mixed (M+2 = Co, Ni, and Cu) ions with λmax for Co, Ni, and Cu ions are  510,425 and 814 nm 56.66%, 77.00%, and 27.23%, respectively. The Antimicrobial activity of V2O5NPs in three concentrations, 25%, 50%, and 75%, was tested against Escherichia coli, Staphylococcus aureus, and Candida albicans fungus. The results of the inhibition of vanadium oxide nanoparticles against positive and negative bacteria were compared with the standard drug Amoxicillin and the results of fungus inhibition with the standard drug Metronidazole. It was found that nano-oxide is more effective at 75% concentration.